Suicidal tendencies and attitude towards freedom to choose suicide among Lithuanian schoolchildren: results from three cross-sectional studies in 1994, 1998, and 2002 - Zaborskis Apolinaras; Zemaitiene Nida (BMC, 2005)
Abstract Background Suicidal behaviour is increasingly becoming a phenomenon associated with young people and an important public health issue in Lithuania. However, there are very few studies evaluating impact of young peoples' attitudes towards suicide to their suicidal behaviour. A better understanding of the relations among the variables associated with suicidal ideation and threats in the normal population of adolescents may eventually result in a better understanding of the more serious forms of adolescent suicidal behaviour. The aim of the present study was to evaluate prevalence of suicidal tendencies among Lithuanian schoolchildren and to estimate its association with an attitude towards suicide in 1994 - 2002. Methods Three country representative samples of schoolchildren, aged 11, 13 and 15, were surveyed in 1994 (n = 5428), 1998 (n = 4513), and 2002 (n = 5645) anonymously in conformity with the methodology of the World Health Organization Cross - National study on Health Behaviour in School-aged Children (HBSC). Results About one third of respondents reported about suicidal ideation, plans or attempts to commit suicide. In the study period of eight years, the percentage of adolescents who reported sometime suicidal ideation decreased but the percentage of adolescents who declared serious suicidal behaviour remained on the same high level (8.1%, 9.8% and 8.4% correspondingly in 1994, 1998 and 2002). Moreover, the number of suicidal attempts changed from 1.0% in 1994 to 1.8% in the year 1998 and to 1,7% in the year 2002. The schoolchildren's attitude towards suicide became more agreeable: 36.6%, 41.9% and 62.5% of respondents, correspondingly in 1994, 1998 and 2002, answered that they agree with a person's freedom to make a choice between life and suicide. A multiple logistic regression analysis with low level of suicidality and high level of suicidality versus non suicidal behaviour as dependent variables for gender, age, year of the survey and attitude towards freedom to choose suicide as independent variables approved a significant association between studied covariates over the entire study period. Conclusion Suicidal tendencies are quite frequent among Lithuanian adolescents. An increasing number of schoolchildren are expressing an agreeable attitude towards suicide. The approving attitude towards suicide among adolescents correlates with suicidal ideation and behaviour.